2007
DOI: 10.1038/cr.2007.28
|View full text |Cite
|
Sign up to set email alerts
|

In vitro derivation of functional insulin-producing cells from human embryonic stem cells

Abstract: The capacity for self-renewal and differentiation of human embryonic stem (ES) cells makes them a potential source for generation of pancreatic beta cells for treating type I diabetes mellitus. Here, we report a newly developed and effective method, carried out in a serum-free system, which induced human ES cells to differentiate into insulin-producing cells. Activin A was used in the initial stage to induce definitive endoderm differentiation from human ES cells, as detected by the expression of the definitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
223
1
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 300 publications
(236 citation statements)
references
References 27 publications
6
223
1
4
Order By: Relevance
“…Recently, using an approach similar to that used for the induction of pancreas from the animal caps of Xenopus embryos, a few groups have succeeded in using RA and activin to differentiate from murine ES cells a pancreaslike tissue that contains endocrine cells, exocrine cells, and duct-like structures (Shi et al, 2005;Jiang et al, 2007;Nakanishi et al, 2007). These advances show that the experimental system using animal caps of Xenopus is a useful tool to screen for novel substances that promote the differentiation of vertebrate stem cells into endodermal tissues and organs.…”
Section: In Vitro Pancreas-induction Systems Using Undifferentiated Xmentioning
confidence: 99%
“…Recently, using an approach similar to that used for the induction of pancreas from the animal caps of Xenopus embryos, a few groups have succeeded in using RA and activin to differentiate from murine ES cells a pancreaslike tissue that contains endocrine cells, exocrine cells, and duct-like structures (Shi et al, 2005;Jiang et al, 2007;Nakanishi et al, 2007). These advances show that the experimental system using animal caps of Xenopus is a useful tool to screen for novel substances that promote the differentiation of vertebrate stem cells into endodermal tissues and organs.…”
Section: In Vitro Pancreas-induction Systems Using Undifferentiated Xmentioning
confidence: 99%
“…Significant progresses have been made in directing human ESCs to differentiate into pancreatic progenitors and insulin-producing beta cells by stepwise induction [2][3][4][5][6][7][8]. However, although pancreatic progenitors can be efficiently generated from human ESCs, efficient in vitro differentiation into mature functional beta cells that are able to reverse diabetes in animal models has not been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In the final, fourth stage cells were transferred into maturation medium containing nicotinamide and IGF2 and cultured for 5 days and without IGF2 for another 2 days to generate IPCs. Flow cytometric analysis indicated that only about 4 % of cells were positive for C-peptide (Jiang et al 2007a).…”
Section: Differentiation Of Embryonic Stem Cellsmentioning
confidence: 99%
“…The question is in what way the immature endocrine cells implanted into heterotopic environment, such as the epididymal fat pads, subcutaneous tissue or under kidney capsule differentiate into pancreatic cells. Jiang et al (2007a) differentiated ESCs into IPCs using four-stage protocol. In the first stage, ESCs were differentiated into definitive endoderm via treatment with sodium butyrate and activin-A for 7 days.…”
Section: Differentiation Of Embryonic Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation